Principal technology leadership practices, teacher ICT competency, and teacher acceptance of School Management System (SMS) in Negeri Sembilan secondary schools / Leong Mei Wei - Leong, Mei Wei (2017)
This study aims to investigate teachers’ perception on the level of principal technology leadership practices, teacher ICT competency, and teacher acceptance and use of School Management System (SMS) in Negeri Sembilan secondary schools. This is a non-experimental quantitative research using survey technique through the administration of a questionnaire that comprised of four sections (teacher demographic variables, principal technology leadership practices, teacher acceptance and use of SMS, and teacher ICT competency) to collect data. The selection of samples for this study was conducted in several stages using probability sampling procedure that involved proportional stratified random sampling, simple random sampling, and systematic random sampling. From a total of 450 questionnaires distributed to the respondents, 417 valid questionnaires were returned representing a valid response rate of 92.7%. The findings showed that teachers among secondary schools in Negeri Sembilan perceived that their principals as demonstrating a high level of technology leadership practices, and teachers rated themselves to have a high level of ICT competency, and acceptance and use of SMS. Furthermore, data indicated that there were statistically significant positive and moderately strong relationships that exist between principal technology leadership practices, teacher ICT competency, and teacher acceptance and use of SMS. In addition, the multiple regression analysis showed that digital citizenship and visionary leadership are the two principal technology leadership practices dimensions that are statistically significant predictors of teacher acceptance and use of SMS, while digital citizenship and systemic improvement being the two principal technology leadership practices dimensions that are statistically significant predictors of teacher ICT competency. Smart pedagogy, professional growth and leadership, and digital citizenship and responsibility are the three teacher ICT competency dimensions that are statistically significant predictors of teacher acceptance and use of SMS in Negeri Sembilan secondary schools. The mediation analysis using SEM showed a partial positive mediating effect of teacher ICT competency on the relationship between principal technology leadership practices and teacher acceptance and use of SMS. The moderating effect test revealed that teacher demographic variables (gender, age, educational level, teaching experience and experience in using computer) were not statistically significant moderators to the relationship between principal technology leadership practices and teacher acceptance and use of SMS in Negeri Sembilan secondary schools. Finally, a new model comprising principal technology leadership practices, teacher ICT competency and teacher acceptance and use of SMS have been derived from the findings of this present study. This study has highlighted that two important human factors, individual (teacher ICT competency) and contextual (principal technology leadership), in predicting teacher acceptance and use of SMS. Besides, several invaluable implications and contributions for academics and practitioners are revealed in this study. This study has contributed significantly to the general body of knowledge in education and particularly educational technology integration. It concludes by presenting a model comprising principal technology leadership practices, teacher ICT competency, and teacher acceptance and use of SMS that suggests for more researches in the related field in the Malaysian educational setting.